(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. “A tradition under threat”. Antropologia della paura e tendenze esclusiviste delle comunità dominanti - 2. La tradizione filosofica del pensiero costituzionale: Williams, Madison e i princìpi cardine della tradizione di “religious fairnes” - 3. Forme di Benign Establishment: critica alla tesi della “presunta innocuità” e interpretazione autentica del principio di separazione - 4. Neutralità statale e speciale considerazione del fenomeno religioso: un rapporto problematico. ABSTRACT: Nussbaum is one of the prominent defenders of the North American liberal tradition, threatened by the post-modern tendency to the exaltation of elements from the mainstream religion and the creation of in-groups between citizens. In his writings, the philosopher reproposes the value of liberal tradition by trying to show the impossibility to justify even the most venial forms of the benign establishment, as in the case of state-sponsored-religious-displays. The article focuses on Nussbaum’arguments, in a critical perspective.